2021
DOI: 10.1098/rsta.2020.0409
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and reproducibility in computational science: implementing validation, verification and uncertainty quantification in silico

Abstract: One contribution of 15 to a theme issue 'Reliability and reproducibility in computational science: implementing verification, validation and uncertainty quantification in silico'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…UQ is an established domain in applied mathematics and engineering but has been notably absent inter alia from the analysis of computer simulations performed using electronic structure and molecular simulation methods. At this time, we are witnessing unified developments in quantifying uncertainty in computer simulation across a wide range of domains including weather, climate, material, fusion, molecular and biomedical sciences [713].…”
Section: Introductionmentioning
confidence: 99%
“…UQ is an established domain in applied mathematics and engineering but has been notably absent inter alia from the analysis of computer simulations performed using electronic structure and molecular simulation methods. At this time, we are witnessing unified developments in quantifying uncertainty in computer simulation across a wide range of domains including weather, climate, material, fusion, molecular and biomedical sciences [713].…”
Section: Introductionmentioning
confidence: 99%
“…The term "scientific reproducibility" of experimental results and observations and theories means that the reliability of these data does not depend on who produces them, but rather, the same findings should be obtained by anyone performing similar procedures. 576 Coveney and co-authors observed that for computer modelling, three factors assess the reliability of calculations to be compared with existing experimental measurements and to make predictions for which no experimental data are available: (a) validation, namely, the confirmation that the results are in agreement with experiment; (b) verif ication that the software does what it is supposed to do and does not contain any errors arising from an incorrect implementation or incorrect numerical methods; and (c) uncertainty quantification to identify the source of errors within the model, for instance systematic errors due to parameter estimation. 576 In classical MD simulations, the lack of reproducibility depends primarily on the intrinsically chaotic nature of the 577 There are two sources of errors in this type of simulations emerging from random and systematic sources.…”
Section: Molecular Modelling and Experiments: A Synergistic And Neces...mentioning
confidence: 99%
“…Practical efforts to realize a quantum computer introduce many additional physical processes, identified here as noise, that complicate the operational description above. [5][6][7][8] In all cases, an important question is to understand whether the resulting computational output is accurate, reproducible and stable. We next consider these notions in the presence of quantum channels that model noisy operations.…”
Section: Theorymentioning
confidence: 99%